Mental health literacy in primary care: Canadian Research and Education for the Advancement of Child Health (CanREACH). Issue 4 (22nd July 2017) - McCaffrey, Eden S N; Chang, Samuel; Farrelly, Geraldine; Rahman, Abdul; Cawthorpe, David
Abstract : The effectiveness of a continuing education programme in paediatric psychopharmacology designed for primary healthcare providers was objectively measured based on the assumption that training would lead to measurable changes in referral patterns and established clinical measures of referred patients. Using established, valid and reliable measures of clinical urgency embedded in to a regional healthcare system since 2002, the referrals to child and adolescent psychiatric services of physicians who participated in the training (n=99) were compared pretraining and post-training, and to non-participating/untrained referring physicians (n=7753) making referrals over the same time period. Referrals were analysed for evidence of change based on frequencies and measures of clinical urgency. Participants of the training programme also completed standardised baseline and outcome self-evaluations. Congruent with participants self-reported evaluative reports of improved knowledge and practice, analysis of referral frequency and the clinical urgency of referrals to paediatric psychiatric services over the study period indicated that trained physicians made more appropriate referrals (clinically more severe) and reduced referrals to emergency services. Quantitative clinical differences as completed by intake clinicians blind to referrals from the study group designations were observed within the trained physician group pretraining and post-training, and between the trained physician group and the unexposed physician group. The results illustrate a novel model for objectively measuring change among physicians based on training in paediatric mental health management.